Altered frontocingulate activation during aversive interoceptive processing in young adults transitioning to problem stimulant use - Stewart, Jennifer L.; Parnass, Jason M.; May, April C.; Davenport, Paul W.; Paulus, Martin P. (Frontiers in Systems Neuroscience, 2013)
Problems associated with stimulant use have been linked to frontocingulate, insular, and thalamic dysfunction during decision-making and alterations in interoceptive processing. However, little is known about how interoception and decision-making interact and contribute to dysfunctions that promote the transition from recreational drug use to abuse or dependence. Here, we investigate brain activation in response to reward, punishment, and uncertainty during an aversive interoceptive challenge in current and former stimulant (cocaine and amphetamine) users using functional magnetic resonance imaging (fMRI). Young adults previously identified as recreational users (n=184) were followed up three years later. Of these, 18 individuals progressed to problem stimulant use (PSU), whereas 15 desisted stimulant use (DSU). PSU, DSU, and 14 healthy comparison subjects (CTL) performed a two-choice prediction task at three fixed error rates (20%=reward, 50%=uncertainty, 80%=punishment) during which they anticipated and experienced episodes of inspiratory breathing load. Although groups did not differ in insula activation or subjective breathing load ratings, PSU exhibited lower right inferior frontal gyrus (IFG) and bilateral anterior cingulate (ACC) activation than DSU and CTL during aversive interoceptive processing as well as lower right IFG in response to decision making involving uncertainty. However, PSU exhibited greater bilateral IFG activation than DSU and CTL while making choices within the context of punishing feedback, and both PSU and DSU showed lower thalamic activation during breathing load than CTL. Findings suggest that frontocingulate attenuation, reflecting reduced resources devoted to goal maintenance and action selection in the presence of uncertainty and interoceptive perturbations, may be a biomarker for susceptibility to problem stimulant use.